"I never told anyone until the #metoo movement": What can we learn from sexual abuse and sexual assault disclosures made through social media?. (May 2020) - Alaggia, Ramona; Wang, Susan
Abstract: Background: Social media is providing new avenues for survivors to disclose sexual abuse and/or assault. Since the creation of #MeToo (2017), and the larger MeToo movement founded by American activist Tarana Burke in 2006, millions are disclosing sexual assaults and past childhood sexual abuse on-line. Objective: Social media for disclosing the highly stigmatized problem of sexual abuse/assault was studied to build knowledge about on-line disclosures. Participants and Setting: Participants were tweeters and posters on Twitter and Reddit. Purposive sampling captured on-line sexual abuse/assault disclosures from September 28, 2018 to October 16, 2018 for thematic analysis. Method: Using a phenomenological design 171 social media posts were analyzed for deeper understanding into new options for disclosing sexual abuse and/or sexual assault. Posts were independently coded by the authors. Sampling was stopped when categorical saturation was reached with no new information coming forward on the research question. Results: Themes that emerged showed the MeToo/#MeToo movement is precipitating sexual abuse/assault disclosures on social media in unprecedented ways; posters identified internal barriers, mixed responses from family, and friends/peers, as well as variable responses from professionals. While some conditions for sexual abuse/assault disclosures have improved, barriers still exist. Conclusion: Social media represents an environmental shift for disclosing sexual violence. Sexual abuse/assault survivors have found voice through social media after periods of silence and being silenced, turning to posting on-line when people and systems have failed to validate and support them. Further investigation is needed on the impacts of on-line sexual abuse and/or assault disclosures.